PkM Pemberdayaan Masyarakat dan Edukasi Pola Hidup Bersih dan Sehat: Menuju Gaya Hidup Berkelanjutan yang Sehat dan Bermakna - Aksir, Muh. Ilham; Juhanis, Juhanis; Sudirman, Akbar; Haeril, Haeril; Hasmyati, Hasmyati (Jurnal Pengabdian Olahraga Masyarakat, 2023)
Changes in people's lifestyles are challenges and opportunities in efforts to improve quality of life and sustainability. People tend to shift to simpler, more sustainable and healthier lifestyles. Modern lifestyle changes, including unhealthy diets, lack of physical activity, and exposure to unhealthy environments, have led to an increase in non-communicable diseases such as obesity, diabetes, cardiovascular disease, and respiratory diseases. This condition indicates the need to change lifestyle to become healthier and more sustainable. Some problems occur due to lack of public awareness and understanding, limited infrastructure and access, social and economic disparities, program sustainability, and unstable behavior changes. In an effort to overcome the problems that have been raised, the solutions that will be implemented are continuous outreach and education, strengthening infrastructure and access, community empowerment, cultural and local context-based approaches, capacity development of partners and workforce, sustainability plans, and monitoring and evaluation. routine. Furthermore, community service activities are carried out using workshop and socialization methods with the results of increasing community awareness, changing lifestyles, increasing the level of community health, community empowerment, reducing environmental impacts, increasing social welfare, increasing community involvement, disseminating knowledge and experience, and quality of life.